Investigating the potential for transisomerisation of trycresyl phosphate with a palladium catalyst and its implications for aircraft cabin air quality. (January 2019) - Megson, David; Hajimirzaee, Saeed; Doyle, Aidan; Cannon, Frank; Balouet, Jean-Christophe
Abstract: The quality of aircraft cabin air has been an area of concern for several decades. Many investigations have linked the presence of organophosphates in air to Aerotoxic Syndrome with adverse symptoms reported by thousands of aircraft crew across the globe. Currently the source of organophosphates has been under debate, with studies pointing towards tricresylphosphates (TCP) in aircraft oil as the main source due to leaks in engine seals resulting in fumes entering the cabin. However, comparisons of oil and cabin samples have shown that the cabin samples contain a much higher proportion of ortho-substituted TCP than is commonly detected in oil. The aim of this experiment was to investigate the potential for palladium catalysts (present in aircraft air conditioning systems) to convert meta- and para-substituted TCP to produce ortho-substituted TCP through transisomerisation. This experiment was performed in a controlled laboratory setting aimed to represent the conditions likely to be experienced in aircraft. Samples were introduced to a stainless steel micro reactor tube containing the pelletized palladium catalyst using a HPLC pump with a 0.2 ml/min feed flow rate. The temperature maintained at 400 °C over a period of 1 h and samples collected using a condensing vesicle. These were then diluted and transferred to a 2 mL vial for analysis by gas chromatography mass spectrometry. No evidence supporting the transisomerisation of tricresylphosphate was obtained. This indicates that more emphasis should be placed on identifying other potential sources of ortho substituted TCP. Highlights: Transisomerisation of TCP did not occur. No ortho substituted TCP created by palladium based catalyst. Further credible sources of ortho TCP should be investigated.